Kepemimpinan dalam Manajemen Keberlanjutan di Era Digital: Pendekatan dan Strategi - Junaidi Adinata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The purpose of this study is to explore the role of leadership in sustainability management in the digital age, focusing on approaches and strategies that organizations can implement to achieve sustainability goals. This study aims to identify the challenges and opportunities faced by leaders in integrating sustainability principles into their business strategies and analyze the impact of digital technology on sustainability practices. The methodology used in this study is a qualitative approach with case study analysis of various organizations that have successfully implemented sustainability management in the digital age. Data were collected through in-depth interviews with organizational leaders, document analysis, and employee surveys to understand their perceptions of leadership and sustainability. In addition, this study also involved secondary data analysis from annual reports and sustainability-related publications. The results show that effective leadership in sustainability management in the digital age requires a deep understanding of technology and its impact on the environment and society. Leaders who are able to adopt digital technology and utilize data for strategic decision-making can create added value for the organization and contribute to sustainability goals. Furthermore, this research also involved secondary data analysis from annual reports and sustainability-related publications. The results show that effective leadership in sustainability management in the digital age requires a deep understanding of technology and its impact on the environment and society. Leaders who are able to adopt digital technology and utilize data for strategic decision-making can create added value for the organization and contribute to sustainability goals. Furthermore, this study found that collaboration between various stakeholders, including government, communities, and the private sector, is crucial for achieving holistic sustainability. This research is expected to provide insights for organizational leaders in formulating more effective sustainability strategies in the digital age.